PENGARUH SIKAP KERJA, KOMITMEN PROFESI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI INSPEKTORAT DAERAH KABUPATEN LABUHANBATU SELATAN - Lely Fitria Harahap; Suriadi .; Lilis Nurhasanah; Herdian Ridha; Dwina Sri Wahyuni (Universitas Islam Sumatera Utara, 2020)
The problems in research what is influence of job attitude on performance. What is influence of profession commitment on performance. What is influence of job motivation on performance. What is influence of job attitude, profession commitment and job motivation on performance. The research of purposes is for know and analysis influence of job attitude on performance. For know and analysis influence of profession commitment on performance. For know and analysis influence of job motivation on performance. For know and analysis influence of job attitude, profession commitment and job motivation on performance. Samples in the research amount to 31 employees people. Data analyze technique in the research using descriptive analyze and regression analize. The results of this research explain of job attitude variable effect significant and positive on performance. Profession commitment variable effect significant and positive on performance. Job motivation variable effect significant and positive on performance. Job attitude, profession commitment and job motivation variable effect significant and positive on performance.